The Effect of Increment Reconstruction Variations in Ct-Scans of Head Trauma on the Contrast to Noise Ratio (CNR) in the Radiology Department of the Prof. Dr. M.A. Hanafiah General Hospital, SM Batusangkar - Dewilza, Nerifa; Sari, Oktavia Puspita; Yudha, Sagita; Farrahin, Balqis Maysan (PT. Hafasy Dwi Nawasena, 2026)
Computed Tomography (CT) is an essential imaging modality for evaluating head trauma due to its ability to provide detailed cross-sectional images. Image quality, particularly the Contrast to Noise Ratio (CNR), plays an important role in diagnostic accuracy. This study aimed to determine the effect of reconstruction increment variations on CNR values in head trauma CT examinations and to identify the increment that provides the most optimal image quality. This research was a quantitative experimental study conducted at the Radiology Unit of RSUD Prof. Dr. M.A. Hanafiah, SM Batusangkar, in February 2025. The population consisted of all patients who underwent CT brain examinations with clinical head trauma during the study period, totaling 12 patients, of whom five patients were selected as samples using purposive sampling. Secondary image data were reconstructed using two increment variations, 0.7 mm and 1 mm, with identical scanning parameters. CNR values were calculated using Radiant Viewer by measuring regions of interest (ROI), and the data were analyzed using the Shapiro–Wilk normality test followed by the Independent Samples T-Test. The results showed that the mean CNR value for the 0.7 mm increment was 304.52, which was higher than the 1 mm increment with a mean CNR of 288.51. However, statistical analysis demonstrated no significant difference between the two increment variations (p = 0.155; p > 0.05). In conclusion, both reconstruction increments produce comparable image quality in head trauma CT examinations. Nevertheless, the 0.7 mm increment provides higher CNR values and may be considered more optimal for improving image clarity